Economic impact of a rapid, on‐demand ADAMTS‐13 activity assay for the diagnosis of thrombotic thrombocytopenic purpura. Issue 4 (20th May 2022) - White, Alicia; Martin, Rosie; Sew, Keven; Stucke, Amanda; Cook, Rob
Abstract: Background: Thrombotic thrombocytopenic purpura (TTP) is a rare, life‐threatening thrombotic microangiopathy (TMA), characterized by ADAMTS‐13 activity <10%. ADAMTS‐13 activity assays are typically performed in reference laboratories with a turnaround time of several days. First‐line treatment for TTP, therapeutic plasma exchange (TPE), typically starts while results are pending. The automated, on‐demand HemosIL AcuStar ADAMTS‐13 Activity assay provides results in under an hour, which could reduce unnecessary TPE use and associated costs. Objectives: To estimate the hospital budget impact in the United States, United Kingdom, and France of using a rapid ADAMTS‐13 activity assay. Methods: We compared routine use of a rapid assay in adults with TMA with a scenario in which results take 3 days. Model structure and variables were based on published literature, plus survey and interviews of five clinicians from the three countries. Costs for the ADAMTS‐13 activity assays and TPE were included. Results: Model results suggest that if an on‐demand, rapid ADAMTS‐13 activity assay is used, US, UK, and French hospitals could save 18 million, £1.2 million, and €1.6 million annually, respectively. This equates to 10 788, £3497, and €4700 saved per patient with TMA in the United States, United Kingdom, and France. The model is most sensitive to the exact split of diagnoses of TMA cases, as savings accrue from non‐TTP diagnoses. Conclusions: In patients with TMA, use of a rapid, on‐demand ADAMTS‐13 activity assay such as the HemosIL AcuStar ADAMTS‐13 Activity assay has the potential to be cost saving for hospitals.